Adsorption of marine phycotoxin okadaic acid on a covalent organic framework - Salonen, Laura M. (2017)
Phycotoxins, compounds produced by some marine microalgal species, can reach high concentrations in the sea when a massive proliferation occurs, the so-called harmful algal bloom. These compounds are especially dangerous to human health when concentrated in the digestive glands of seafood. In order to generate an early warning system to alert for approaching toxic outbreaks, it is very important to improve monitoring methods of phycotoxins in aquatic ecosystems. Solid-phase adsorption toxin tracking devices reported thus far based on polymeric resins have not been able to provide an efficient harmful algal bloom prediction system due to their low adsorption capabilities. In this work, a water-stable covalent organic framework (COF) was evaluated as adsorbent for the hydrophobic toxin okadaic acid, one of the most relevant marine toxins and the parental compound of the most common group of toxins responsible for the diarrhetic shellfish poisoning. Adsorption kinetics of okadaic acid onto the COF in seawater showed that equilibrium concentration was reached in only 60 min, with a maximum experimental adsorption of 61 mg g1. Desorption of okadaic acid from the COF was successful with both 70% ethanol and acetonitrile as solvent, and the COF material could be reused with minor losses in adsorption capacity for three cycles. The results demonstrate that COF materials are promising candidates for solid-phase adsorption in water monitoring devices.